Snake-Bite with Disseminated Intravascular Coagulation (DIC) and Stage II Hypertension - Hendra Subroto; Leni Lismayanti (Journal of Medicine and Health, 2017)
Snake-bite is an important medical emergency case and caused of many hospitaladmission especially in the rural area, forests, plantations and swamps. Despite its importance,there have been fewer proper data of snake-bite incidence in Indonesia. World HealthOrganization estimate that at least 421,000 envenomings and 20,000 deaths from snakebitesoccur each year, especially in South and South East Asia and sub-Saharan Africa. The authorsreport a case of a 76-year-old man came to Hasan Sadikin Hospital with chief complaint woundin his right hand and right forearm from snake-bite. Snake-bites can cause DIC because thevenom activates the coagulation system and cause fibrinolysis which occurs in less than 24hours. Laboratory results, we found abnormalities such as anemia, thrombocytopenia,hypofibrinogenemia, and increased levels of D-dimer. Patients were treated for 8 days and thenallowed to go home. Snake-bite is an occupational disease of farmers, plantation workers,herdsmen, fishermen, other. Snake bite cases require prompt and comprehensive managementso as to minimize the possibility of disability and death.Keywords: snake bite, DIC, hypertension